(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of nursing students and nurses in the care of users with nephrostomy Method: an experience report study carried out in 2021 in a reference center for stoma patients in a city in southern Brazil, and selected data on users with nephrostomy, analyzing the reason for seeking care with the stoma therapist nurse during the nursing consultation. Results: difficulties were observed in performing self-care associated with the change of the collecting system, because the location of the ostomy does not favor the adequate fixation of the bag in front of the user’s own attempt to change the collecting equipment, always depending on another person to perform this change. The service users report that even with the aid of mirrors, the maneuver to be used makes it impossible to properly position the collection equipment, favoring leaks and decreasing the useful time of the collection bags. Final considerations: The professional nurse must evaluate the person with nephrostomy, the conditions of the stoma and the peristomal skin, prescribing the collecting equipment and adjuvants best suited for each case, the position of the collecting bag must allow its emptying by the user, and it is necessary to train family members to assist in the exchanges.